Obesity and the labour market: a comparative study of the European Health Interview Survey - Benítez-Llamazares, Nuria (My University, 2018)
Obesity has been defined by the World Health Organization (WHO) as an “abnormal or excessive fat accumulation that presents a risk to health”. The increasingly growing rates of obese people in the last few decades (remarkably in developed countries), has raised concerns among researchers and national health systems, and the analysis of its causes and consequences for human health has become a priority. Similarly, in socioeconomic investigation we find that obesity has been considered as a key factor for living conditions from a social and economic perspective. In previous research, we analysed if being obese had an impact on the probability of participating in the Spanish labour market, using data taken from the first edition of the European Health Interview Survey (EHIS 2009). Our results indicated that high rates of BMI (obesity) implied lower probabilities of occupational participation, especially for working-age females living in Spain. The aim of this study is to continue our work, using data taken from the second edition of the European Health Interview Survey (EHIS 2014). Same, body mass index (BMI) is being used as an indicator for nutritional status, and we carry out both a descriptive and an econometric analysis using probit and tobit models for limited dependent variables (LDV). We intend to compare the results from both surveys lengthwise.
Keywords: Obesidad; Mercado de trabajo